Overview of Stroke Technique Skills Among Badminton Athletes at PB New Binatama Padang - Muhammad Alhamdi Rahmatullah; Ardo Okilanda; Juanda Putra; Eval Edmizal (Jurnal Gladiator, 2026)
Badminton is a sport that requires athletes to master fundamental stroke techniques, including the serve, lob/clear, drive, smash, dropshot, and netting, to achieve optimal performance. Observations at PB New Binatama Padang revealed variations in athletes' technical proficiency and the absence of comprehensive data describing their overall stroke abilities. Therefore, this study aimed to evaluate the stroke technique skills of badminton athletes at PB New Binatama Padang to provide information for improving training programs and athletic performance. This study employed a quantitative approach using a descriptive research design. The sample consisted of 15 athletes selected through the total sampling technique. Data were collected using a badminton stroke skill test and analyzed through descriptive statistics based on established assessment norms. The findings indicated that the athletes' overall stroke technique skills were in the good category, with very high scores in the short and long serves, moderate performance in the lob/clear and smash, high performance in the dropshot, and good performance in netting.